2020
DOI: 10.3390/ijerph17030684
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hydrogen Sulfide in Septic Tanks for Treating Black Water via an Immobilized Media of Sulfur-Oxidizing Bacteria

Abstract: In South Korea, the installation of septic tanks for treating black water (STBW) is regulated even in sewage treatment areas to prevent the black water deposition in combined sewers. STBWs in which black water is anaerobically decomposed generate high concentrations of hydrogen sulfide (H2S). In this study, an immobilized media of sulfur-oxidizing bacteria (SOB) was used to remove the H2S. SOB media was prepared by using activated sludge collected from a wastewater treatment plant. Prior to field application, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In order to evacuate hydrogen sulfide from wastewater treated for the AD process, physicochemical processes such as absorption have been used [ 112 , 113 ], scrubbing [ 114 ], and using water-containing chemicals [ 115 , 116 ]. Nonetheless, these procedures are expensive and can result in chemical waste accumulation.…”
Section: Biological Methodsmentioning
confidence: 99%
“…In order to evacuate hydrogen sulfide from wastewater treated for the AD process, physicochemical processes such as absorption have been used [ 112 , 113 ], scrubbing [ 114 ], and using water-containing chemicals [ 115 , 116 ]. Nonetheless, these procedures are expensive and can result in chemical waste accumulation.…”
Section: Biological Methodsmentioning
confidence: 99%
“…On the other hand, Kang et al [30] showed that sulfide oxidation decreases the pH values in the liquid phase. The latter agrees with our experimental results, since the main pH value in the reactor with zeolite (7.55) was lower than the system without zeolite (7.72).…”
Section: Effect Of Sulfide Pulse On Partial Nitrification In the Systems With And Without Zeolitementioning
confidence: 99%
“…Numerous physicochemical procedures have been in use to eradicate H 2 S from industrial waste gas streams such as absorption (Boumnijel et al, 2016;Taheri et al, 2016), scrubbing , and using chemicals that are water-containing (Kang et al, 2020;. Nonetheless, these operational procedures are costly and induce the production of chemical wastes.…”
Section: Biological Methodsmentioning
confidence: 99%